2021
DOI: 10.26508/lsa.202000811
|View full text |Cite
|
Sign up to set email alerts
|

Modulating HSF1 levels impacts expression of the estrogen receptor α and antiestrogen response

Abstract: Master transcription factors control the transcriptional program and are essential to maintain cellular functions. Among them, steroid nuclear receptors, such as the estrogen receptor α (ERα), are central to the etiology of hormone-dependent cancers which are accordingly treated with corresponding endocrine therapies. However, resistance invariably arises. Here, we show that high levels of the stress response master regulator, the heat shock factor 1 (HSF1), are associated with antiestrogen resistance in breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
1
9
0
1
Order By: Relevance
“…A significant association between high HSF1 expression and increased mortality among the ER-positive breast cancer patients receiving hormonal therapy was first noticed by Santagata et al, 2011 , then confirmed by Gökmen-Polar and Badve, 2016 . It was proposed that overexpression of HSF1 in ER-positive breast cancers was associated with a decreased dependency on the ERα-controlled transcriptional program for cancer growth ( Silveira et al, 2021 ). However, this conclusion was based on experiments performed without estrogen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…A significant association between high HSF1 expression and increased mortality among the ER-positive breast cancer patients receiving hormonal therapy was first noticed by Santagata et al, 2011 , then confirmed by Gökmen-Polar and Badve, 2016 . It was proposed that overexpression of HSF1 in ER-positive breast cancers was associated with a decreased dependency on the ERα-controlled transcriptional program for cancer growth ( Silveira et al, 2021 ). However, this conclusion was based on experiments performed without estrogen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen-dependent cancers are treated with hormonal therapies, and high levels of HSF1 have been associated with antiestrogen resistance (Silveira et al, 2021). It was proposed that overexpression of HSF1 in ER-positive breast cancers was associated with a decreased dependency on the ERα-controlled transcriptional program for cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…It is of great clinical interest to resolve the functions of HSF1 and HSPs in this process. HSF1 may decrease transcription and increase the degradation of ERa (181), while HSP70 and HSP90 can bind to steroid receptors and alter their activity (182). HER2, overexpressed in up to 50% of breast carcinoma cases, is known to promote tumor cell growth.…”
Section: Breast Cancermentioning
confidence: 99%